Agency heads$1 (Bpublic profiles and bureaucratic performances - Lee, Don S. (American Review of Public Administration)
Do agency heads$1 (Bpublic profiles enhance the performance of bureaucratic agencies? Existing studies of public administration emphasize the role of public information in managing government performance. However, whether public attention to agency heads affects the performance of their agencies is largely understudied. Using a unique dataset of agency heads$1 (Bpublic profiles in South Korea, we predict that such profiles have a positive impact on their agencies$1 (Bperformance. Although agency heads are not held accountable directly to citizens, close public attention to agency heads$1 (Bactivities may function as an indirect mechanism of accountability and of improving their organizations$1 (Bperformance. Our analysis supports our prediction and further suggests that an agency head$1 (Bs high public profile is a benefit, particularly in more salient policy areas where (3z(Bgoing public(3y (Bis more effective for their policy reforms. Our findings have clear implications: the importance of agency heads$1 (Bunconventional roles for effective agency management, responding to rapidly changing external environments.- Reproduced s
Keywords: Agency hand, Public profile, Bureaucratic, South Koran